2020
DOI: 10.1111/1750-3841.15450
|View full text |Cite
|
Sign up to set email alerts
|

Pea starch exhibits good expansion characteristics under relatively lower temperatures during extrusion cooking

Abstract: Extrusion processing characteristics of pea starch were studied as impacted by various extrusion cooking processing variables, including, moisture content (15%, 17.5%, and 20% w.b.), temperature (120, 135, and 150°C), and screw speed (150, 200, and 250 rpm), in a co-rotating twin-screw extruder. Physicochemical properties such as radial expansion ratio (ER), unit density (UD), water absorption index (WAI), and water solubility index (WSI) were measured. ER of the extrudates ranged between 2.52 and 3.63. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
(109 reference statements)
1
5
0
Order By: Relevance
“…The ER was highest for all blends at the lowest screw speed, 150 rpm, and decreased as screw speed levels increased. With pea starch, Rangira et al (2020) reported the same trend under similar conditions (17.5% MC at 150, 200, and 250 rpm). This may be attributed to a reduction in the melt elasticity caused by starch degradation.…”
Section: Expansion Ratiosupporting
confidence: 58%
See 3 more Smart Citations
“…The ER was highest for all blends at the lowest screw speed, 150 rpm, and decreased as screw speed levels increased. With pea starch, Rangira et al (2020) reported the same trend under similar conditions (17.5% MC at 150, 200, and 250 rpm). This may be attributed to a reduction in the melt elasticity caused by starch degradation.…”
Section: Expansion Ratiosupporting
confidence: 58%
“…Research has identified potential applications of pea starch in the food industry. Rangira et al (2020) found that pea starch evinced good expansion characteristics under low moisture, temperature, and shear conditions.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…This was similar with the reports that samples with higher GE values had higher water holding capacities (WAI) in extrusion without enzymes (Bhattacharya & Hanna, 1987). However, many researchers reported the WAI of extruded starch without enzymes was higher than that of native starch (de Cruz et al ., 2015; Rangira et al ., 2020). The decrease in WAI of enzymatic extrudates could be attributed to the enzymatic hydrolysis of starch framework (Xu et al ., 2015) (Fig.…”
Section: Resultsmentioning
confidence: 99%